Common Etiologies of Generalized Tooth Mobility: A Review of Literature - K Ghods; A Alaee; A Jafari; A Rahimi (Islamic Azad University, 2022)
Background and Aim: Tooth mobility, which is prevalent among patients seeking dental healthcare services, happens when the tooth is reversibly displaced horizontally or vertically beyond its normal physiological limits. Tooth mobility is classified into 2 subgroups: localized and generalized. Generalized tooth mobility occurs when more than 2 teeth are mobile. In this review, the available studies regarding the common etiologies of generalized tooth mobility are discussed.   Materials and Methods: In this review article, data were collected by reviewing the available articles published between 2011 to 2021 in national and international journals by searching the PubMed, PubMed Central, Medline, EBSCO, Google Scholar, and Embase databases using the key words "Tooth Mobility", "Tooth Movement" "Periodontal Disease", "Systemic Disease", and "Malignant Disease". Among the relevant articles, 51 were chosen. Results: It seems that numerous etiologies, which can be either physiological or pathological, can result in generalized tooth mobility. Conclusion: Since an optimal treatment outcome depends on accurate diagnosis, it is crucial for the dentists to be aware of the common etiologies of this condition.